47.6k views
5 votes
Solve the expression using the correct order of operations.
0.75x3.2+ (9.1)2-((-2.3)-(-0.9))2

User Ahanusa
by
6.1k points

1 Answer

4 votes

Answer:


0.75 * 3.2+ (9.1)^2-((-2.3)-(-0.9))^2 = 83.25

Explanation:

Given


0.75 * 3.2+ (9.1)^2-((-2.3)-(-0.9))^2

Required

Solve

Start with the bracket


0.75 * 3.2+ (9.1)^2-((-2.3)-(-0.9))^2 = 0.75 * 3.2+ (9.1)^2-(-1.4)^2

Evaluate all exponents


0.75 * 3.2+ (9.1)^2-((-2.3)-(-0.9))^2 = 0.75 * 3.2+ 82.81-1.96

Evaluate all products


0.75 * 3.2+ (9.1)^2-((-2.3)-(-0.9))^2 = 2.4+ 82.81-1.96


0.75 * 3.2+ (9.1)^2-((-2.3)-(-0.9))^2 = 83.25

User Halliewuud
by
6.1k points